Teaching Kindness and Compassion: An Exploratory Intervention Study to Support Young Children's Prosocial Skills in an Inclusive ECEC Setting - Katri Pardon; Arniika Kuusisto; Lotta Uusitalo (MDPI AG, 2023)
In this exploratory intervention study, the aim was to teach 5-7-year-old children prosocial skills in an inclusive Finnish early childhood education and care (ECEC) setting. The intervention programme was based on previous studies and helps fill a gap in how to promote prosocial behaviour in an ECEC setting encompassing children with diverse needs. The theoretical framework draws on research on character strengths in the field of positive psychology, particularly what the literature refers to as the strengths of the heart, namely kindness and compassion. The study follows the methodological framework of pragmatism and a mixed-methods research perspective. Research methods include questionnaires and interviews with children (n = 23), some of their guardians (n = 8) and ECEC teachers (n = 2). The results were two-fold. With the picture-based questionnaire, the pre-post measures showed little advancement. However, individual interviews revealed developments in children's prosocial thinking that also translated into concrete actions. These findings were further supported by the positive feedback received from teachers and guardians. The contents of the programme can be integrated into daily, inclusive ECEC pedagogy. Methodologically, the intervention design serves as a starting point for the further development of data collection practices that capture children's voices in ECEC.